PopPlanner: visually constructing demographic models for simulation - Ewing, Gregory B.; Reiff, Pauline A.; Jensen, Jeffrey D. (Frontiers in Genetics, 2015)
Currently there are a number of coalescent simulation programs that support a wide range of features, such as arbitrary demographic models, migration, and sub structure. Defining the model is done typically with either text files or command line switches. Although this has proven to be a powerful method of defining models of high complexity, it is often error prone and difficult to read without familiarity both with command lines and the program in question. A intuitive GUI based population structure program that can both read and write applicable command lines would dramatically simplify the construction, modification, and error checking of such models by a wider user base. Results: PopPlanner is a tool to both construct and inspect complicated demographic models visually with a GUI where the user’s primary interaction is through mouse gestures. Because of their popularity, we focus on ms and by extension msms, command line coalescent simulation programs. Our program can be used to find errors with existing command lines, or to build original command lines. Furthermore the graphical output supports a number of editing and output features including export of publication quality figures.